Penerapan Akuntabilitas Dan Transparansi Dalam Mengelola Keuangan Desa (Studi Kasus Desa Jirak Kecamatan Jirak Jaya Kabupaten Musi Banyuasin) - Nopasari, Widia; Noviardy, Andrian (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Widia Nopasari. Implementing Village Management Financial Transparency and Accountability (Case Study of Jirak Village, Jirak Jaya District, Musi Banyuasin Regency) Following are Mr Andrian Noviardy's instructions. The aim of this research is to determine the accountability and transparency of financial management in Jirak Village. Observations, interviews and documentation were used to collect data. Indicators for each stage of village financial management are used as analytical tools in accordance with Minister of Home Affairs Regulation Number 113 of 2014. Based on the results and discussions that have been carried out, the The end of this exploration is implementation Transparency and Accountability in financial management in Jirak Village has not been implemented well and the Jirak Village Community cannot easily access village financial information due to not implementing Transparency Based on the findings of this research properly. in accordance with the Ministry of Home Affairs Guidelines Number 113 of 2014 concerning Regional Financial Administration. Apart from that, the Jirak Village Government also continues to close community access to information related to village organizations or government.